Design, Implementation, and Evaluation of the Adolescents and Surveillance System for the Obesity Prevention Project. Issue 12 (March 2016) - Tabacchi, Garden; Bianco, Antonino; Alessi, Nicola; Filippi, Anna Rita; Napoli, Giuseppe; Jemni, Monèm; Censi, Laura; Breda, João; Schumann, Nathali Lehmann; Firenze, Alberto; Vitale, Francesco; Mammina, Caterina
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: The Adolescents Surveillance System for Obesity prevention (ASSO) Project aimed at developing standardized and web-based tools for collecting data on adolescents' obesity and its potential determinants. This has been implemented and piloted in the local area of Palermo city, Italy. The aim of the present study is to provide an overview of the Project's design, implementation, and evaluation, highlighting all the aspects for a potential scale-up of the surveillance system on the whole national territory and abroad, as a sustainable and effective source of data. The overall structure and management, the ASSO-toolkit, the ASSO-NutFit software, and all developed and used procedures for recruiting, training, and data collecting/analyzing are addressed. An interim evaluation has been performed through a feasibility study; a final Project evaluation has been performed reporting the Strengths, Weaknesses, Opportunities, and Threats (SWOT) and the attributes that a surveillance system should have. This article provides a detailed overview of the Project and highlights that ASSO can be considered a valid, logical, coherent, efficient, and sustainable surveillance system that is consistent with countries' needs and priorities. The system developed by the ASSO Project provides high-quality data and complies with several characteristics typical of a suitable surveillance system. It has a potential of being adopted within the National Health Service and other countries' Health Services for monitoring adolescents' obesity and its determinants, such as food intakes, behaviors, physical activity, and fitness profiles.